Thymectomy and radiation-induced type 1 diabetes in nonlymphopenic BB rats. - Ramanathan, S; Bihoreau, M; Paterson, A; Marandi, L; Gauguier, D; Poussier, P (2002)
Spontaneous type 1 diabetes in BB rats is dependent on the RT1(u) MHC haplotype and homozygosity for an allele at the Lyp locus, which is responsible for a peripheral T-lymphopenia. Genetic studies have shown that there are other, as yet unidentified, genetic loci contributing to diabetes susceptibility in this strain. BB rats carrying wild-type Lyp alleles are not lymphopenic and are resistant to spontaneous diabetes (DR). Here we show that thymectomy and exposure to one sublethal dose of gamma-irradiation (TX-R) at 4 weeks of age result in the rapid development of insulitis followed by diabetes in 100% of DR rats. Administration of CD4(+)45RC(-) T-cells from unmanipulated, syngeneic donors immediately after irradiation prevents the disease. Splenic T-cells from TX-R-induced diabetic animals adoptively transfer type 1 diabetes to T-deficient recipients. ACI, WF, WAG, BN, LEW, PVG, and PVG.RT1(u) strains are resistant to TX-R-induced insulitis/diabetes. Genetic analyses revealed linkage between regions on chromosomes 1, 3, 4, 6, 9, and 16, and TX-R-induced type 1 diabetes in a cohort of nonlymphopenic F(2) (Wistar Furth x BBDP) animals. This novel model of TX-R-induced diabetes in nonlymphopenic BB rats can be used to identify environmental and cellular factors that are responsible for the initiation of antipancreatic autoimmunity.